Kidney transplant recipients possess less depressing plasma than healthy controls in KwaZulu-Natal (South Africa) – a paradoxical observation - Omarjee, Saleha; Assounga, Alain G (African Journal of Nephrology, 2022)
Background: The reduced activation of lymphocytes of patients on immunosuppressive drugs is well documented. Human plasma has been reported previously to play a role in lymphocyte proliferation. Several factors, including alpha globulin and lipoproteins, have been proposed as modulators of lymphocyte proliferation. Aim: To measure the ATP response of peripheral blood mononuclear cells (PBMCs) from kidney transplant patients and healthy controls following phytohaemagglutinin (PHA) stimulation and to compare the effect of plasma of transplant recipients and of healthy controls on lymphocyte activation. Methods: Peripheral blood mononuclear cells from the blood of healthy controls and kidney transplant patients on regimens based respectively on cyclosporine, sirolimus and tacrolimus, were separated by density gradient centrifugation. Cells were counted and incubated overnight with and without PHA. The luciferin–luciferase enzyme reaction, which induces bioluminescence, and the Turner Biosystem luminometer were used to measure intracellular ATP levels in relative light units, which were converted to ng/mL using an ATP standard curve. A chi-squared test using the Instat 3 program (Graphpad®) was used to compare results. Results: PHA stimulation of PBMC from healthy individuals produced a 47% increase in ATP production. This increase was reduced to 31% when transplant patient plasma was added (P < 0.05). However, when plasma from healthy controls was added instead, paradoxically, the ATP production decreased further to 14%. A similar difference between patient and control plasma was recorded using PBMCs from transplant patients. The reduction in ATP production was the greatest in PBMCs from transplant patients on the tacrolimus-based regimen (P = 0.0388). Receiver operator characteristic (ROC) for ATP level revealed an area under the curve of 0.986. The cut-off value of ATP level between kidney transplant and control using the Youden index was 595 ng/mL, with a sensitivity of 93.3% and specificity of 99.9% Conclusion: Plasma isolated from patients on immunosuppressive drugs suppressed the response of lymphocytes to PHA stimulation. Paradoxically, plasma from healthy controls suppressed T cell activation even more severely. If confirmed in a more extensive study, this observation may be used to influence the choice of replacement fluid in the practice of plasma exchange in transplantation. Keywords: plasma, peripheral blood mononuclear cells, T cell